PERANCANGAN MODEL PENGUKURAN KINERJA CORPORATE SOCIAL RESPONSIBILITY (CSR) DI BPD JATIM - Wilda Khairin Najwah (UNUSA Press, 2021)
Companies that realize the importance of CSR do so to obtain a corporate image, this practice uses social activities for corporate marketing activities. Publication in the media is one of the mediums in obtaining a positive image for the company. BPD East Java has been carrying out CSR activities since 2007 but has a measuring tool such as a special KPI to measure the effectiveness of its CSR activities. So that the purpose of this research is to design a key performance indicator (KPI) of CSR activities at BPD East Java. This research uses a qualitative research method with a modified participation action research (PAR) approach or modified action research, which is carried out to obtain an overview of CSR activities in BPD East Java. Then the researchers made a measuring instrument or KPI to determine the effectiveness of CSR activities using the model: prism performance. The results of the KPI design are then discussed with relevant stakeholders for evaluation. The validation of the BPD East Java BPD CSR KPI is carried out by submitting the KPI design proposal to the company which is considered to understand the object of research with the company's real conditions and has a role in making corporate strategic decisions.